Antenatal dexamethasone use and respiratory distress in late preterm infants: results from first Vietnamese matched cohort study - Tran Tuan Hung Ho; Quang Vinh Truong; Thi Kim Anh Nguyen; Minh Tam Le; Vu Quoc Huy Nguyen (BMC, 2021)
Abstract Background Respiratory distress syndrome (RDS) is one of the leading causes of early neonatal morbidity and mortality in late preterm infants (LPIs) worldwide. This matched cohort study aimed to assess how the antenatal dexamethasone use affect the respiratory distress (RD) proportion in preterm newborns between 34 0/7 weeks and 36 6/7 weeks of gestation. Methods This was a prospective cohort study on 78 women with singleton pregnancy who were in threatened preterm birth and had not received prior dexamethasone, who were admitted between 34 0/7 weeks and 36 6/7 weeks at Hue University of Medicine and Pharmacy Hospital from June 2018 to May 2020. The matched control group without dexamethasone use included 78 pregnant women diagnosed with threatened late preterm births who were at similar gestational ages and estimated fetal weights as the treatment group. The treatment group received 6 mg intramuscular dexamethasone every 12 h for a total of 4 doses or until delivery. Primary outcome was the rate of neonatal RD. Secondary neonatal outcomes included the need for respiratory support, neonatal intensive care unit (NICU) admission, hypoglycemia, necrotizing enterocolitis, intraventricular hemorrhage, and neonatal death. Statistical analyses were performed by using SPSS software, version 26.0. Results The proportion of RD in LPI was significantly lower in the treatment group than in the matched control group (10.3% vs. 23.1%, respectively), adjusted Odds Ratio [aOR] 0.29; 95% confidence interval [CI] 0.10 - 0.83 and p = 0.021. Neonatal hypoglycemia was more common in the dexamethasone group than in the matched group (25.6% vs. 12.8%, respectively; aOR, 2.59; 95% CI, 1.06 - 6.33; p = 0.037). There were no significant between-groups differences in the incidence of respiratory support, NICU admission or length of hospital stay. Conclusions Administration of antenatal dexamethasone to women at risk for late preterm birth could help to lower the proportion of respiratory distress in late preterm infants.